Can 18F-Fluoroestradiol positron emission tomography become a new imaging standard in the estrogen receptor-positive breast cancer patient: A prospective comparative study with 18F-Fluorodeoxyglucose positron emission tomography? - Manoj Gupta; Anupama Datta; Partha Choudhury; Maria Dsouza; Ullas Batra; Anil Mishra (World Journal of Nuclear Medicine)
Correct staging is the most crucial for the treatment outcome in cancer management. Molecular imaging with 18F-fluoroestradiol (FES) positron emission tomography-computed tomography (PET-CT) targets estrogen receptor (ER) and may have a higher incremental value in diagnosis by aiding specificity. We enrolled 12 female breast cancer patients prospectively and did 18F-FES PET-CT and 18F-fluorodeoxyglucose (FDG) PET-CT within 1 week interval time. Lesion detection sensitivity was compared for a total number of lesions and for nonhepatic lesions only by McNemar test. 18F-FES PET-CT was taken as reference in case of indeterminate lesions. The incremental value reported by identifying 18F-FES exclusive lesions and by characterization of 18F-FDG indeterminate lesions. Spearman rank test was used to correlate ER expression and maximum standardized uptake value (SUVmax). Two ER-negative patients with no 18F-FES uptake were excluded. Ten ER-positive patients with 154 disease lesions were finally analyzed. 18F-FDG picked-up 142 lesions (sensitivity 92.21%), whereas 18F-FES picked-up 116 lesions (sensitivity 75.32%) and this difference was statistically significant. For nonhepatic lesions (n = 136) detectability, 18F-FDG picked-up 124 (sensitivity 91.18%), whereas 18F-FES picked-up 116 (sensitivity 85.29%) lesions and this difference was not statistically significant. Beside 12 exclusive lesions, 18F-FES characterized 41 (27.5%) 18F-FDG indeterminate lesions. Overall 18F-FES impacted 20% patient management. The positive trend was also seen with 18F-FES SUVmax with ER expression and negative with 18F-FDG SUVmax. We conclude, 18F-FDG has overall better sensitivity than 18F-FES PET-CT, however for nonhepatic metastasis difference was not significant. 18F-FES PET-CT better-characterized lesions and impacted 20% patient management. Therefore, 18F-FES PET-CT should be used with 18F-FDG PET-CT in strongly ER expressing patients for better specificity.